Motivating Agents: How Much Does the Mission Matter? - Jeffrey P. Carpenter; Erick Gong (Institute for the Study of Labor (IZA), 2013)
Economic theory predicts that agents will work harder if they believe in the mission of the organization. Well-identified estimates of exactly how much harder they will work have been elusive, however, because agents select into jobs. We conduct a real effort experiment with participants who work directly for organizations with clear missions. Weeks before the experiment, we survey potential participants for their organizational preferences. At the experiment, we randomly assign workers to organizations, creating either mission matches or mismatches. We overlay performance incentives to test whether they can make up for the motivational deficit caused by a mismatch. Our estimates suggest that matched workers produce 72% more than mismatched workers and that performance pay can increase output by 35% compared to workers who only receive a base wage. Considering matches and mismatches separately, we find that performance pay has only a modest effect on matched workers (a 13% increase) while it has a large effect (a 86% increase) on mismatches, an effect that erodes much of the performance gap caused by the poor match. Our results have broad implications both for those organizations already with well-defined missions (i.e., compensation and screening policies) as well as for those organizations strategizing about strengthening or clarifying their missions.
Keywords: C91; J22; J33; M52; 330; principal-agent; mission; incentive; labor supply; experiment